Impact Of Earnings And Debt Information On Investor Behavior - Adi, Sunu Prasetya; Addury, Multazam Mansyur (Universitas Ahmad Dahlan, 2021)
Information from company publications can be an initial signal for investors to buy shares in the company. The earnings information can be an indicator for investors to assess and predict profits for companies and investors in the future. This study aims to analyze the impact of earnings and debt information on investor behavior in buying shares. This study uses the LQ45 company object on the Indonesia Stock Exchange. The data used in the form of annual from 2014 to 2018. Research data analysis techniques used are descriptive analysis and panel data regression. The results found that the earnings information variable measured by net profit has a positive and significant effect on investor behavior as measured by the company's sales volume at a significance level of 5%. The debt information variable measured by DER has no significant effect on investor behavior as measured by the company's sales volume.